Development, implementation and evaluation of a Cognitive Behavioural Therapy based intervention programme for the management of anxiety symptoms in South African children with visual impairments - Visagie, Lisa S. (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.